(untitled) (Research, Society and Development, 2024)
Osteosarcopenia is a musculoskeletal disorder, in which bone mass, microarchitectural of bone, muscle mass, strength, and performance decrease significantly with age. The majority of osteosarcopenia is experienced by the elderly, sedentary population, as well as patients who have comorbidities that affect the musculoskeletal system or interfere with physical activity. This article aims to present a study on osteosarcopenia in geriatric patient. Osteoporosis represents a major health problem contributing to millions of fractures worldwide, whereas sarcopenia is associated with metabolic outcomes and physical decline. Both diseases affect physical and social function, confidence, and the patient’s quality of life. Osteosarcopenia is the term when both conditions occur concomitantly. Interactions between both conditions may accelerate individual disease progression, which is associated with higher morbidity from falls, fractures, disability as well as mortality.